2018
DOI: 10.1016/j.psychsport.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis of the irrational Performance Beliefs Inventory (iPBI) in a sample of amateur and semi-professional athletes

Abstract: Objectives. This investigation sought to test the construct validity of the irrational performance beliefs inventory (iPBI) in a sample of amateur and semi-professional athletes. Method. In total, 550 athletes (312 men, 212 women, M age = 38.04 ± 13.80 years) completed the iPBI and demographic questions at a single time point. Results. Confirmatory factor analysis showed lower than acceptable fit indices for the 28-item iPBI (comparative fit index [CFI] = .84). After removal of potential problem items, a 20-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
9
35
0
2
Order By: Relevance
“…The confirmatory factor analysis revealed that the scale has acceptable fit (Byrne, 2010;Hu & Bentler, 1999;Kline, 2011). This finding is similar to the findings of the original form (Turnet et al, 2016) and of the short form (Turner & Allen, 2018) of the scale. The correlation coefficient between sport anxiety, sport perfectionism and irrational beliefs were investiagted for the construct validity of scale.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The confirmatory factor analysis revealed that the scale has acceptable fit (Byrne, 2010;Hu & Bentler, 1999;Kline, 2011). This finding is similar to the findings of the original form (Turnet et al, 2016) and of the short form (Turner & Allen, 2018) of the scale. The correlation coefficient between sport anxiety, sport perfectionism and irrational beliefs were investiagted for the construct validity of scale.…”
Section: Discussionsupporting
confidence: 91%
“…The internal consistency coefficients of the scale factors and the total score indicate that the scale were highly reliable (Field, 2009). These finding are consistent with the ones of the original form of the scale (Turner & Allen, 2018). The corrected item total correlation coefficient of the scale indicates that the items of the scale are distinctive (Büyüköztürk, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…There are several important things that happen by considering the fit model in the SEM (Structural Equation Modeling) results. First, the bigger or closer to the criteria specified for each category, then this will also affect item validity and overall reliability (Turner & Allen, 2018). The second classification of the goodness of fit index criteria is based on the output that produces criteria based on absolute fit, namely scores on GFI and RMSEA, then incremental fit scores on AGFI, NFI, CFI, IFI, and RFI, while the last is criteria in parsimonious fit, namely PGFI, PNFI, and AIC.…”
Section: Discussionmentioning
confidence: 99%
“…The main aims of the present study were to translate the iPBI into Thai language and to test the validity and reliability of the T-iPBI in a Thai sample. Future researchers should extend these aims and recruit more specific samples to examine the validity THE T-IPBI and reliability of the T-iPBI in groups such as athletes (Turner & Allen, 2018), occupational workers (Turner et al, 2018a), and students (Turner et al, 2018b). In an East Asian culture, rationality is also highly valued as the essence of human life.…”
Section: Discussionmentioning
confidence: 99%